Clinicopathological features and surgical treatments of intraductal papillary neoplasm of the bile duct: a case report and literature review - Fu, Chang; Jin, Hengwei; Wang, Yongxin; Xu, Hongji (Frontiers in Medicine, 2024)
Intraductal papillary neoplasm of bile duct (IPNB), as a precancerous lesion of cholangiocarcinoma, is a rare biliary tract tumor. A 66-year-old female patient was found to have a bile duct mass by routine examination. The liver function tests and tumor markers were normal. Imaging findings revealed a 2.6 cm mass in the common hepatic duct, accompanied by dilatation of both intrahepatic and extrahepatic bile ducts. The patient underwent open extrahepatic bile duct resection, cholecystectomy and Roux-en-Y hepaticojejunostomy. We also conducted a literature review to summarize the clinicopathological features and surgical treatments of IPNB.